Sifat Adsorptif dan Termodinamika Ekstrak Lignin dari Pelepah Nipah (Nypa fruticans Wurmb) untuk Korosi Baja Lunak dalam Medium HCl - Hilda Sartika; Emriadi; Yeni Stiadi; Suryati Suryati (Jurnal Fisika Unand, 2024)
Research on the adsorptive and thermodynamic properties of lignin extract from Nipah fronds (Nypa fruticans Wurmb) for mild steel corrosion in hydrochloric acid medium has been conducted. The inhibititon effect of lignin extract from Nipah (Nypa fruticans Wurmb) fronds (LENF) on the corrosion of mild steel in HCl solution was studied by weight loss and optical microscopy methods. The results show that LENF was a good inhibitor in 1.0 M HCl, and the inhibition efficiency increases with increasing concentration of the extract and temperature. Inhibitive effect was afforded by the adsorption of the extract on the steel surface, which was found to accord with Langmuir adsorption isotherm. Adsorption and activation parameters such as activation energy (Ea), enthalpy (∆Η), free Gibbs energy (∆G), and entropy (∆S) were evaluated on the corrosion and inhibition process.